PENYELESAIAN WANPRESTASI ANGGOTA KOPERASI PEGAWAI KEMENTERIAN KOORDINATOR BIDANG PEREKONOMIAN DALAM PERJANJIAN PEMINJAMAN UANG - Purba, Mayesti Estelita; Mariane, Irene (Tribuere, 2023)
The Employee Cooperative of the Coordinating Ministry for Economic Affairs is a cooperative formed based on equal status as employees. This certainly increases the management's confidence in providing loans to members because there is a guarantee that they will carry out their obligations in good faith. The Cooperative Management recorded the number of defaults from 2018 to 2023 amounting to IDR 2,447,570,868.33,- with the number of members who defaulted as many as 90 people. The main issues that will be raised in this research are how to resolve defaults by members of the Employee Cooperative of the Coordinating Ministry for Economic Affairs in money lending agreements and what efforts are made by the management of the Employee Cooperative of the Coordinating Ministry for Economic Affairs if the efforts to resolve the default that have been made do not bring the expected results. This thesis was written using descriptive normative legal research methods, using primary and secondary data, analyzed qualitatively and drawing conclusions based on deductive logic. From the results of the research carried out, it was concluded that the settlement efforts carried out by the Coordinating Ministry for Economic Affairs Employee Cooperative management were non-litigation efforts or out-of-court settlements that prioritized the principle of kinship, namely notification of loan arrears, sending letters of warning, rescheduling or rescheduling, cutting deposits, and persuasive efforts, namely debt collection by the chairman of the cooperative management. However, if the efforts made by the savings unit management have not brought the expected results, the cooperative management can cut salaries, re-implement auto-debit, re-implement principal and mandatory savings, establish collateral, monitor loan repayment regularly, apply the principles of healthy lending. , as well as implementing the 3Rs, namely rescheduling (rescheduling debt payment times), reconditioning (readjusting the terms of money loan agreements), and restructuring (rearranging with additional loan facilities).